On homotopy nilpotency of the octonian plane OP^2 - Golasi´nski, Marek (MATHEMATICA SCANDINAVICA, 2021)
Let OP^2_(p) be the p-localization of the Cayley projective plane OP^2 for a prime p or p=0. We show that the homotopy nilpotency class nil Ω(OP^2_(p))<∞ for p>2 and nil Ω (OP^2_(p))=1 for p>5 or p=0. The homotopy nilpotency of remaining Rosenfeld projective planes are discussed as well.